Early maladaptive schemas, coping strategies, and functional impairments in individuals with adjustment disorder during compulsory military service: a comparison with healthy controls - Sağlam, Tarık (Frontiers in Psychiatry, 2025)
BackgroundAdjustment Disorder (AD) is a psychological condition that arises as a response to identifiable stressors, leading to emotional distress and functional impairment. This cross-sectional study, conducted within the context of compulsory military service in Turkey, aimed to investigate the association between early maladaptive schemas (EMS), coping strategies, and functional outcomes in individuals diagnosed with AD. The study population consisted of male conscripts who developed AD symptoms following relocation and psychosocial stressors specific to the military setting, such as loss of autonomy, limited support, and institutional pressure. EMS are deep-seated cognitive patterns that shape an individuals’ responses to stress and may contribute to the development of AD. However, the relationship between EMS, coping strategies, and functional outcomes in AD remains unclear.MethodsThis cross-sectional study, included 113 male participants diagnosed with Adjustment Disorder and 75 healthy male controls, aged between 18 and 40 years. The clinical group consisted of male conscripts who developed AD symptoms during their mandatory military service. The participants completed self-report measures, including the Young Schema Questionnaire (YSQ-SF3), Coping Attitudes Inventory (CAI, a self-report instrument designed to assess coping strategies), and Functionality Assessment Short Test (FAST). The groups were compared and correlations between EMS, coping strategies, and functionality were examined using statistical tools.ResultsParticipants with AD scored significantly higher on maladaptive schemas, particularly in failure, enmeshment/dependence, and pessimism, showed greater use of avoidance-based coping strategies, and exhibited poorer overall functioning compared to healthy controls (p <.001, η² = .072–.384). Maladaptive schemas were negatively correlated with adaptive coping (r = –.389 to –.565) and positively associated with avoidance and functional impairment (r = .573 to.734, p <.01).ConclusionsOur findings suggest that maladaptive schemas may play a key role in how individuals with AD cope with stress, often leading to avoidance behaviors and functional decline. Addressing these schemas through schema-focused therapy may help individuals develop healthier coping strategies and improve overall functioning. Further research, including randomized controlled trials evaluating schema-focused interventions, is needed to explore long-term treatment outcomes, particularly in populations exposed to institutional or occupational stressors such as compulsory military service.